2011
DOI: 10.1159/000321591
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anticholinergic Activity in Serum on Clinical Symptoms of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is well known as a disease characterized by degeneration of cholinergic neuronal activity in the brain. It follows that patients with AD would be sensitive to an ‘anticholinergic burden’, and also that medicine with anticholinergic properties would promote various clinical symptoms of AD. Despite the relevance of this important phenomenon to the clinical therapeutics of AD patients, few reports have been seen concerning the relationship between anticholinergic burden and clinical AD sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 39 publications
2
44
0
1
Order By: Relevance
“…Recently, it has been suggested that AA might appear not only with exogenous manner, but also with an endogenous manner and AA appeared by means of inflammation [8] and mental stress [9]. We reported a positive relationship between SAA and clinical symptoms of AD patients [1,2]. Among 76 AD patients, 26 AD patients were positive for SAA [SAA (+)], the mean SAA value in the SAA (+) group was 4.14 ± 2.70 nM and the remaining 50 patients were negative [SAA (-)].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Recently, it has been suggested that AA might appear not only with exogenous manner, but also with an endogenous manner and AA appeared by means of inflammation [8] and mental stress [9]. We reported a positive relationship between SAA and clinical symptoms of AD patients [1,2]. Among 76 AD patients, 26 AD patients were positive for SAA [SAA (+)], the mean SAA value in the SAA (+) group was 4.14 ± 2.70 nM and the remaining 50 patients were negative [SAA (-)].…”
Section: Discussionsupporting
confidence: 47%
“…We already reported that anticholinergic activity (AA) can occur endogenously in patients with Alzheimer's Disease (AD) [1]. Since there is a possibility that AA might accelerate the pathologic changes of AD (amyloid plaques and tau protein) [2], it is important to establish treatment for abolishing AA.…”
Section: Introductionmentioning
confidence: 99%
“…SAA is considered to be an indicator of net anticholinergicity, combining the effects of anticholinergic agents and endogenous anticholinergic activity 13 . Our results suggest that among patients with schizophrenia, elevated SAA may indicate and predict an inhibitory effect on the extrapyramidal motor symptoms except for involuntary movements.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between atropine concentration and 3 H -QNB counts was linear for atropine concentrations ranging from 1.95 pmol / ml to 25 pmol / ml. Participants with SAA levels greater than 1.95 pmol / ml were de ned as SAA positive 13 .…”
Section: Participantsmentioning
confidence: 99%
“…5 Moreover, we have also reported the possibility that AA appeared endogenously in Alzheimer's patients. 6 Therefore, it is possible that AA could accelerate the pathology of PD. As such, we believe that in PD or LBD AA also appears endogenously and accelerates the PD pathology, increasing Lewy bodies.…”
mentioning
confidence: 99%